Empathy Development in Early Grade at State Elementary Schools - Muh Shaleh (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
This study aims to measure and inform the level of empathy (affective and cognitive) of early grade students aged 6-8 years at SDN Baruga Kendari, Southeast Sulawesi. Seven schools were selected as the sample based on a methodology called Random Sampling. The sample in this study were children aged 6-8 years, totaling 150 students. The research method used in this research is quantitative research. The data collection technique is to use a questionnaire applied to collect data about the development of children's empathy. The questionnaire refers to children's empathy using the GEM (Griffith Empathy Measure) scale, which is designed to assess a child's level of empathy for the conditions they are experiencing. Criteria scores for each statement were "yes" and "no" and were analyzed using IBM SPSS Statistics 2. The results showed that in general the empathy of early grade students aged 6-8 years at SDN Baruga Kendari Southeast Sulawesi was more oriented towards affective/cognitive empathy . This research implies that empathy in children aged 6-8 years is still developing so that more attention is needed to maximize the development of children's empathy.